Museum Morsbroich : Malerei - Plastik - Objekte : 1985. - Städtisches Museum Morsbroich, Leverkusen (Leverkusen : Stadt Leverkusen, 1985)
Agam, Yaacov ; Albers, Josef ; Alfano, Carlo ; Alviani, Getulio ; Anuskiewicz, Richard Joseph ; Arakawa, Shusaku ; Bak, Imre ; Bandau, Joachim ; Bandau, Joachim ; Barth, Carl ; Barth, Wolf ; Baukhage, Gerd ; Boehle, Hilmar ; Brüning, Peter ; Bucher, Franz ; Calder, Alexander ; Calderara, Antonio ; Cane, Louis ; etc.
boek